Reduced lung elastic recoil and fixed airflow obstruction in asthma. Issue 6 (3rd September 2019) - Tonga, Katrina O.; Chapman, David G.; Farah, Claude S.; Oliver, Brian G.; Zimmermann, Sabine C.; Milne, Stephen; Sanai, Farid; Jetmalani, Kanika; Berend, Norbert; Thamrin, Cindy; King, Gregory G.
ABSTRACT: Background and objective: Fixed airflow obstruction (FAO) in asthma occurs despite optimal inhaled treatment and no smoking history, and remains a significant problem, particularly with increasing age and duration of asthma. Increased lung compliance and loss of lung elastic recoil has been observed in older people with asthma, but their link to FAO has not been established. We determined the relationship between abnormal lung elasticity and airflow obstruction in asthma. Methods: Non‐smoking asthmatic subjects aged >40 years, treated with 2 months of high‐dose inhaled corticosteroid/long‐acting beta‐agonist (ICS/LABA), had FAO measured by spirometry, and respiratory system resistance at 5 Hz (Rrs5 ) and respiratory system reactance at 5 Hz (Xrs5 ) measured by forced oscillation technique. Lung compliance (K) and elastic recoil (B/A) were calculated from pressure–volume curves measured by an oesophageal balloon. Linear correlations between K and B/A, and forced expiratory volume in 1 s/forced vital capacity (FEV1 /FVC), Rrs5 and Xrs5 were assessed. Results: Eighteen subjects (11 males; mean ± SD age: 64 ± 8 years, asthma duration: 39 ± 22 years) had moderate FAO measured by spirometry ((mean ± SD z‐score) post‐bronchodilator FEV1 : −2.2 ± 0.5, FVC: −0.7 ± 1.0, FEV1 /FVC: −2.6 ± 0.7) and by increased Rrs5 (median (IQR) z‐score) 2.7 (1.9 to 3.2) and decreased Xrs5 : −4.1(−2.4 to −7.3). Lung compliance (K) was increased in 9 of 18 subjects and lung elastic recoil (B/A) reduced in 5 of 18 subjects. FEV1 /FVC correlated negatively with K (rs = −0.60, P = 0.008) and Rrs5 correlated negatively with B/A (rs = −0.52, P = 0.026), independent of age. Xrs5 did not correlate with lung elasticity indices. Conclusion: Increased lung compliance and loss of elastic recoil relate to airflow obstruction in older non‐smoking asthmatic subjects, independent of ageing. Thus, structural lung tissue changes may contribute to persistent, steroid‐resistant airflow obstruction.Clinical trial registration: ACTRN126150000985583 at anzctr.org.au (UTN: U1111‐1156‐2795) Abstract : We measured lung elastic recoil, spirometry and the forced oscillation technique in older non‐smoking asthmatic subjects with fixed airflow obstruction (FAO). In addition to airway remodelling, FAO can be attributed to reduced lung elastic recoil. Identification of the mechanisms leading to loss of lung elasticity may offer new targets for intervention. See related Editorial